Cidades saudáveis e qualidade de vida em Uberlândia (MG): aportes metodológicos para um processo em construção - Alves, Lidiane Aparecida (2016)
The current study includes theoretical and methodological reflections on the quality of life in the city of Uberlândia, Minas Gerais. It started from the thought that the quality of life is multifactorial and is permanently under construction and the main objective of analyzing it as one of the componets of Healthy Cities's moviment. The theoretical research focused on the concepts of healthy cities, quality of life, health, sustainability, well-being, happiness, indexes and indicators. From the use of multiple search strategies, documentary and on field of quantitative and qualitative character, this research of exploratory descriptive nature can offers a contribution to the studies on the quality of life in cities. It is proposed that the studies startes to work with some concept, like some notions os life quality adequated for some paticular reality, whose notions can approach concepts already established as health. This step is important on the exploratory researches. The studies may include aspects of objective analysis, subjective or both. The objective dimension, which is most common approach, are traditionally considered variables and indicators related to: the urban infrastructure (health, education, leisure, security, mobility), dwelling (quantitative and qualitative dwlling deficit), the urban structure (density and mix uses), socioeconomic characteristics (age, income, education), urban infrastructure (sanitation, communication), governance (social mobilization and participation). To focus on the subjective dimension, most recent and unusual, it is proposed to consider the (dis)satisfaction, the personal assessment in relation to the objective aspects. In conclusion, being intrinsically related to the health, the quality of life also has a number of determinants, and the ideal of the reach of quality of life depends on the action of all citizens based on the recognition of networks and territories, in a interescalar perspective and intersectoral. Therefore, emphasis in given on the potential of tools, such as the observatories, to monitor and intervent in reality, aiming in a building process of healthy cities.